Águas subterrâneas, evolução dos sistemas técnicos de explotação na aluvião do Rio Jaguaribe em São João do Jaguaribe-CE no contexto do uso e ocupação do solo - Pinheiro, Antonio Flávio Costa (2021)
This dissertation analyzes the alluvium in the Lower Jaguaribe River, in São João do Jaguaribe-CE (State of Ceará), considering the historicity of spatial production, in relation to the socioeconomic dynamics at the interface of the technical evolution of water exploitation at this groundwater level of 57.96 km². This is an investigation carried out in the field and laboratory between July 2019 and January 2020. The general objective of the investigation was to study the groundwater intake systems and the quality of groundwater in the area through physicochemical analysis, in the interface usage-land occupation. 827 wells were mapped, with 817 (98.91%) of the wells recorded in the alluvium and only 10 (1.09%) in the Crystalline. Systematizing the wells by category, 21.91% are tubular, 38.80% are ravines and 39.29% are mixed. They are shallow wells (phreatic) with an average depth of 8.72 m, a maximum of 21.40 m and a minimum of 1.55 m. Static level with an average of 4.30 m, a maximum of 14.30 m and a minimum of 0.05 m. The water columns (water depth) with an average of 4.45 m, a maximum of 13.00 m and a minimum of 0.15 m. For the qualitative water evaluation, physicochemical analysis and 30 samples were carried out. In the physicochemical water analysis, in addition to larger cations and anions such as sodium (Na+ ), potassium (K+ ), calcium (Ca++), magnesium (Mg++), chloride (Cl- ), sulfate (SO4 = ), bicarbonate (HCO3 - ) were also determined, fundamental in the calculation of the ionic balance, hydrogen ionic potential (PH), total dissolved solids (STD), electrical conductivity (EC), in addition to silica (SiO2), hardness, total hardness, alkalinity, alkalinity in bicarbonate, total alkalinity (CaCO3 - ), the nitrogen series: (NH3), nitrite (HNO2), nitrate (NO3 - ), total ammonia nitrogen (N-NH3); fluoride (F-1 ), total iron (Fe), turbidity (UNT), aluminum (Al+3), reactive phosphate (PO4 - ). Most of the samples are within the values allowed by the Consolidation Ordinance No. 5 issued on September 28, 2017 by the Ministry of Health (MS) and CONAMA Resolution No. 396/2008, with remarked anomalies in the total iron, chloride and turbidity parameters. According to the U.S.S.L Diagram, 50.00% of the SE samples fall under "C2 - S1", presenting a medium risk of salinization and low risk of sodium, suitable for almost all crops. 26.66% are included in “C3 - S1” (13%) and “C3 - S2” (13%), they present a high risk of salinization and a medium risk of sodium. C2-S are considered to have a medium salinity risk, should be used with caution, and can be used in silty-sandy, silty or sandy clayey soils when there is moderate leaching from the soil. It seems that technological development, despite having favored a greater use of surface and groundwater with greater flow and economic productivity, small and medium-sized agricultural activities characterized by orchards were reduced due to the high costs of electricity, indebtedness with technological packages that have been contaminating the soil and water, including some houses (those that can buy and are aware of the risks) are supplied with bottled water to drink, which means that the whole situation is a breakdown of the metabolism of material exchange and energy in the man-ground relationship.